Securing the User Registration Process in an IP Telephony System Using Blockchain and KYC Technologies - Ousmane, Abdoul Matine; DJARA, Tahirou; BELLO, ABDOU WAHIDI (My University, 2024)
In this article, we develop a solution for securing IP telephony networks. The solution developed is based on revolutionary blockchain technology and uses KYC, facial recognition and OTP techniques to secure the various levels of user interaction with the ToIP network (enrolment, authentication, communication session, post-communication session). A comparative study, based on the Ethereum and Hyperledger Fabric blockchains, enabled us to select Hyperledger Fabric as the development framework for our blockchain. The criteria justifying our choice are essentially: the modularity of the architecture, the variety of programming languages for smarts contracts, the possibility of creating private channels between network members, high access control and data confidentiality, as well as a flexible consensus model. These criteria are crucial, as they guarantee both the robustness and flexibility of the network in a shared communication data context. To guarantee data confidentiality, access rights management and transaction speed, we opted for a private blockchain developed under the Hyperledger Fabric framework.
Keywords: Blockchain; Hyperledger fabric; IP telephony; KYC; Security; Voice over IP